2006
DOI: 10.1111/j.1467-8659.2006.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Garments: A Fully Geometric Approach for Clothing Design

Abstract: Figure 1: From sketch to garment. Left to right: sketched contours and darts; 3D shape computed using distance field; piecewise developable surface; final virtual garment, compared with the real one sewn from the 2D patterns we output. AbstractModeling dressed characters is known as a very tedious process. It usually requires specifying 2D fabric patterns, positioning and assembling them in 3D, and then performing a physically-based simulation. The latter accounts for gravity and collisions to compute the rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 28 publications
1
126
0
Order By: Relevance
“…Other research has looked at designing useable interfaces for rapid and intuitive design of new patterns [Volino and Magnenat-Thalmann 2005;Umetani et al 2011]. Researchers have also looked at sketch-based interfaces for designing garments and other 3D objects composed of 2D pieces [Decaudin et al 2006;Turquin et al 2007;Mori and Igarashi 2007;Igarashi et al 2008b;Volino et al 2009;Robson et al 2011]. …”
Section: Prior Workmentioning
confidence: 99%
“…Other research has looked at designing useable interfaces for rapid and intuitive design of new patterns [Volino and Magnenat-Thalmann 2005;Umetani et al 2011]. Researchers have also looked at sketch-based interfaces for designing garments and other 3D objects composed of 2D pieces [Decaudin et al 2006;Turquin et al 2007;Mori and Igarashi 2007;Igarashi et al 2008b;Volino et al 2009;Robson et al 2011]. …”
Section: Prior Workmentioning
confidence: 99%
“…Where la 9 = (1,2,3 waist level ratio x 3 hem level ratio x 4 design ease at hip x 5 hem width ratio x 6 flag x 7 style point level ratio x 8 style width ratio Table3.Output parameter for silhouette Parameters Description y 1 vertical scale y 2 ease at hip y 3 hip ease ratio y 4 to define key style elements y 5 to define different silhouette and key style elements y 6 to define style point y 7 to define key style elements The sketch design model based on the knowledge of fashion design is developed to describe the characteristics of a skirt by using parameters so as to create various skirts and to overcome the impractical designs. As shown in Figure 2, this sketch design model is composed of five portions: skirt silhouette shape, waist level and waist style, skirt length and hem style, key style elements, and additional detail features.…”
Section: 1sketch Design Modelmentioning
confidence: 99%
“…Meghna and Barbara [18] developed a method called "human ranks", which provides feedback to designs by using 5-point scale (i.e., [1][2][3][4][5]. The advantage of this method lies in its accuracy.…”
Section: Selection Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers tried to focus on geometric technique for producing surface pieces that cover the cloth bending. They also provide sewing typical in deformation weave design and stitching effect like in real world [3]. Mongus et al have suggested a method to simulate various fabrics (cotton, spandex, wool or silk) by considering its structure, weight and other factors [4].…”
Section: Introductionmentioning
confidence: 99%